Estimation of the anisotropy parameters of transversely isotropic shales with a tilted symmetry axis - Nadri, D.; Sarout, J.; Bona, Andrej; Dewhurst, D. (Blackwell Publishing Ltd, 2012)
This paper reports a new approach for the estimation of Thomsen anisotropy parameters and symmetry axis orientation from ultrasonic P-wave traveltime measurements on transversely isotropic shale samples of arbitrary geometry. This approach can be used for core samples cut in any direction with respect to the bedding plane, because no a priori assumption regarding the symmetry axis orientation is made. This orientation is rather part of the solution of the inverse problem together with the anisotropy parameters themselves. Very fast simulated reannealing is used to search for the best possible estimate of the model parameters. The methodology is applied to spherical and cylindrical anisotropic shale samples.